Anmeldelser - Davidsen, Markus; Elgvin, Torleif; Müller, Mogens; Petersen, Anders Klostergaard; Sedgwick, Mark; Sørensen, Jesper; Thomsen, Søren Feldtfos; Warburg, Margit; Østergaard, Jesper (Religionsvidenskabeligt Tidsskrift, 2012)
n/a